ASESMEN PEMBELAJARAN SEJARAH BERBASIS ONLINE UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS DAN ANALITIS - fahruddin, fahruddin (Universitas Negeri Malang, 2025)
The objectives of this research are: (1) to develop an online-based history learning assessment design that meets high standards in terms of accessibility, completeness of assessment components, and visual appearance, and (2) to develop an online-based history learning assessment design with a high level of effectiveness in measuring students' critical and analytical thinking skills. This study employs an experimental method, with data collection conducted through questionnaires, interviews, and observations involving history teachers and eleventh-grade social science students at SMAN 1 Yogyakarta, SMAN 1 Godean, and SMAN 1 Bantul. The data analysis employs parametric statistics and an independent t-test to compare the experimental and control groups, determining the effectiveness level of the assessment design. The results of this study are as follows: (1) The developed online-based history learning assessment design has demonstrated high standards of accessibility, with a score of 19.21 and an achievement rate of 90%; completeness of assessment components, with a score of 18.11 and an achievement rate of 91.67%; and visual appearance, with a score of 17.66 and an achievement rate of 91.67%. (2) The developed online-based history learning assessment design has been proven effective, as indicated by a significance value of 0.00 < 0.05, confirming its effectiveness in measuring students' critical and analytical thinking skills. This effectiveness is further supported by improvements across six critical and analytical thinking indicators, which were higher in the experimental group than in the control group. These findings suggest that the proposed assessment design is viable and suitable for assessing students' critical and analytical thinking skills.